Genotypic variability studies and identification of pre-harvest sprouting tolerant wild Vigna - LAMICHANEY, AMRIT; PRATAP, ADITYA; KATIYAR, PARDIP KUMAR; SINGH, NARENDRA PRATAP (The Indian Journal of Agricultural Sciences, 2021)
Seed dormancy is the main component of domesticated traits, loss of which results into rapid and uniform germination, synchronous maturity and ease in harvesting. However, breakdown or loss of fresh seed dormancy (FSD) has made seeds vulnerable to pre-harvest sprouting (PHS). Though, seeds of Vigna species are protected by pod, these are still susceptible to PHS. Identification of donor(s) having short duration of FSD (30-45 days) has become utmost important to transfer the trait to high yielding varieties. The wild progenitors and wild relatives of the cultivated Vigna offer a source of several useful traits; therefore, the experiment was initiated to understand the level of variation in PHS and fresh seed germination (FSG) in wild accessions of Vigna species. PHS and FSG among 59 Vigna accessions ranged between 0-100%, with a mean of 55.86% and 61.19%, respectively. Five accessions (IC276983, IC349701, Trichy Local 1, LRM/13-33 and LRM/13-26) of Vigna trilobata and one accession (IC251440) of Vigna sublobata recorded no pod loss due to PHS with 0% FSG (2.5% in V. sublobata). Seed size showed a positive association with PHS, where smaller seeds (100-SW 2 g, respectively). The accessions identified, especially V. sublobata (crossing compatible) could be used as a source of PHS tolerance to transfer dormancy in Vigna species, particularly in mungbean and urdbean.